How Does Urbanization Affect Citizens’ Pro-Environment Behavior? A Hierarchical Analysis of the Chinese General Social Survey - Qing, Wen; Wang, Yibao; Zhang, Yanbo; Han, Jingwen; Li, Cuixi (Frontiers in Environmental Science, 2022)
Many studies have focused on the pressure of urbanization on resources and environment, but few have explored the positive effect of urbanization on reducing environmental pressure from the perspective of urbanization affecting pro-environment behavior (PEB). To systematically explore the impact of urbanization with different dimensions on PEB, this study establishes a hierarchical theoretical framework and conducts empirical test based on the data of Chinese General Social Survey (CGSS) and China City Statistical Yearbook (CCSY) as well as a hierarchical linear model (HLM). The results reveal the following: First, urbanization can directly influence PEB and the four dimensions of urbanization (economic, social, spatial and population urbanizations) can influence PEB in different manners. Economic urbanization can positively influence private PEB; social urbanization exerts a slightly positive impact on PEB; spatial urbanization has a notably negative impact on PEB while population urbanization has no significant effect on PEB. Second, Urbanization also indirectly affects PEB by influencing individual characteristic variables. Social and economic urbanizations positively moderate the relationship between social interaction and PEB. The research results illustrate the relationship between urbanization and PEB, and can guide how to promote PEB in the process of urbanization.